2018
DOI: 10.1144/sp482.5
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase flow and underpressured shale at the Bruce nuclear site, Ontario, Canada

Abstract: Hydraulic testing has revealed dramatic underpressures in Paleozoic shales and carbonates at the Bruce nuclear site in Ontario. Although evidence from both laboratory and field studies suggests that a small amount of gas-phase methane could be present in the shale, previous studies examining causal linkages between the gas phase and the underpressure have been inconclusive. To better elucidate processes in such a system, we used a highly simplified 1D representation of the site to test, by using iTOUGH2-EOS7C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…For the zones in which gas phase was introduced, the van Genuchten 1/P 0 parameter was increased by a factor of 2, as justified by the uncertainty analysis conducted by Plampin and Neuzil (2018), which showed that varying this parameter by a factor of 2 in either direction from the fitted value effectively captured the spread in the measured capillary pressure characteristics of samples from the relevant Table 1 Porous Media Properties Used in the iTOUGH2-EOS7C Simulations Note. The three layers of the model consisted of the "tight" region in the middle, bounded above, and below by the Guelph and Cambrian aquifers.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the zones in which gas phase was introduced, the van Genuchten 1/P 0 parameter was increased by a factor of 2, as justified by the uncertainty analysis conducted by Plampin and Neuzil (2018), which showed that varying this parameter by a factor of 2 in either direction from the fitted value effectively captured the spread in the measured capillary pressure characteristics of samples from the relevant Table 1 Porous Media Properties Used in the iTOUGH2-EOS7C Simulations Note. The three layers of the model consisted of the "tight" region in the middle, bounded above, and below by the Guelph and Cambrian aquifers.…”
Section: Methodsmentioning
confidence: 99%
“…This was done by developing a simple representation of the site that extends from 0.37 to 0.86 kmBGS-the entire region of the subsurface in which anomalous pressures have been observed-to which the rock properties listed in Table 1 were assigned. The domain was initially homogeneous, with most of the rock property values set equal to those of the "tight" region of the model developed by Plampin and Neuzil (2018). The boundaries of the model domain were applied at the locations of the Guelph and Cambrian aquifers, as indicated by the horizontal dashed gray lines in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations